2002
DOI: 10.1038/sj.onc.1205334
|View full text |Cite
|
Sign up to set email alerts
|

WRN helicase accelerates the transcription of ribosomal RNA as a component of an RNA polymerase I-associated complex

Abstract: Werner syndrome (WS) is a rare autosmomal recessive genetic disorder causing premature aging. The gene (WRN) responsible for WS encodes a protein homologous to the RecQ-type helicase. WRN has a nucleolar localization signal and shows intranuclear tra cking between the nucleolus and the nucleoplasm. WRN is recruited into the nucleolus when rRNA transcription is reactivated in quiescent cells. Inhibition of mRNA transcription with a-amanitin has no e ect on nucleolar localization of WRN whereas inhibition of rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 47 publications
2
69
1
Order By: Relevance
“…Both mRNA and rRNA synthesis are indeed downregulated in cells from WS patients. 36,37 The exonuclease and unwinding activity of the WRN helicase can also act upon RNA-DNA heteroduplexes, which may explain its role in transcription and subsequent cell proliferation and survival. 38 A defect in overall RNA levels and synthesis in WS fibroblasts may not be rescued by hTERT, despite the ability of hTERT to extent the replication capacity of WS cells.…”
Section: Why Do Cells That Lack Wrn Senesce In Response To Myc?mentioning
confidence: 99%
“…Both mRNA and rRNA synthesis are indeed downregulated in cells from WS patients. 36,37 The exonuclease and unwinding activity of the WRN helicase can also act upon RNA-DNA heteroduplexes, which may explain its role in transcription and subsequent cell proliferation and survival. 38 A defect in overall RNA levels and synthesis in WS fibroblasts may not be rescued by hTERT, despite the ability of hTERT to extent the replication capacity of WS cells.…”
Section: Why Do Cells That Lack Wrn Senesce In Response To Myc?mentioning
confidence: 99%
“…The detailed procedure was described previously. 21) RESULTS Genotoxic Effect of E2 and BPA DNA damage in MCF-7 cells was assessed by measuring the CTL. E2 was added at concentrations from 10 Ϫ9 to 10 Ϫ7 M, which induced Comet formation after 3 h, after which the CTL increased dose dependently (Table 1).…”
Section: Chemicalsmentioning
confidence: 99%
“…Moreover, Laine et al (3) have shown that WRN stimulates topoisomerase I DNA-unwinding activity that could influence cellular transcription. The yeast WRN homologue, SGS1, also participates in DNA replication and RNA pol I-dependent transcription (4), and the WRN helicase enhances RNA pol I-dependent transcription of ribosomal RNA (5).…”
mentioning
confidence: 99%